Extreme absorption enhancement in ZnTe:O/ZnO intermediate band core-shell nanowires by interplay of dielectric resonance and plasmonic bowtie nanoantennas - Nie, Kui-Ying (Sci Rep, 2017)
Intermediate band solar cells (IBSCs) are conceptual and promising for next generation high efficiency photovoltaic devices, whereas, IB impact on the cell performance is still marginal due to the weak absorption of IB states. Here a rational design of a hybrid structure composed of ZnTe:O/ZnO core-shell nanowires (NWs) with Al bowtie nanoantennas is demonstrated to exhibit strong ability in tuning and enhancing broadband light response. The optimized nanowire dimensions enable absorption enhancement by engineering leaky-mode dielectric resonances. It maximizes the overlap of the absorption spectrum and the optical transitions in ZnTe:O intermediate-band (IB) photovoltaic materials, as verified by the enhanced photoresponse especially for IB states in an individual nanowire device. Furthermore, by integrating Al bowtie antennas, the enhanced exciton-plasmon coupling enables the notable improvement in the absorption of ZnTe:O/ZnO core-shell single NW, which was demonstrated by the profound enhancement of photoluminescence and resonant Raman scattering. The marriage of dielectric and metallic resonance effects in subwavelength-scale nanowires opens up new avenues for overcoming the poor absorption of sub-gap photons by IB states in ZnTe:O to achieve high-efficiency IBSCs.